Kinetic Comparison between Drop Jumps and Horizontal Drop Jumps in Elite Jumpers and Sprinters - Raynier Montoro-Bombú; Paulo Miranda-Oliveira; Maria João Valamatos; Filipa João; Tom J. W. Buurke; Amândio Cupido Santos; Luís Rama (Applied Sciences, 2024)
Previous research addressed the spatiotemporal variables of the drop jump (DJ) versus the horizontal drop jump (HDJ). This study compared the kinetic variables of the DJ versus the HDJ in elite jumpers and sprinters. In a single session, sixteen elite jumpers and sprinters performed two DJ attempts with three different fall heights (0.30 m, 0.40 m, and 0.50 m), and after 2 h, performed two HDJ attempts from the same fall heights (0.30 m, 0.40 m, and 0.50 m). Kinetic variables: eccentric ground reaction forces (GRFE) and concentric ground reaction forces; eccentric impulse (PE) and concentric impulse (PC); peak power in the concentric phase; and rate of force decrease (RFDe) were measured using a research-grade force plate. The Wilcoxon test was used to compare the vertical and anteroposterior axes. GRFE was significantly higher (p ≤ 0.05) in the DJ vs the HDJ with large effect sizes. The PE (p ≤ 0.006) and PC (p = 0.002) were significantly lower in the DJ than in the HDJ. The RFDe was also significantly lower in the DJ at 0.30 m vs. the HDJ at 0.30 m (p = 0.002). In summary, elite jumpers and sprinters may benefit from incorporating both the DJ and the HDJ into their training regimens, with the DJ being particularly advantageous for enhancing power metrics and RFDe.